(Re)Gaining Our Voice: Future of Marketing in Australasia. Issue 3 (August 2022) - Conduit, Jodie; Lu, Vinh; Veer, Ekant
Marketing academia in Australasia is facing unprecedented challenges to ensure the relevance and impact in modern business practices and public policy making. This crisis in identity and professional pressures suggest we must pay significant attention to nurturing the mental, emotional, and social well-being of academics; protecting those most vulnerable; and championing our cause. To be at the forefront of institutional decision-making, the academy must act decisively and proactively. In this commentary, we argue that the future shape of the academy will require collective engagement of academics within the Australasian community, driven by a shared vision with society embedded as the central tenant of universities around which research and education activities are focused. Individual alignment with this vision will be fundamental, facilitated by collaborative ways of working and shared resource investments across universities, businesses, and society. For this future vision to be realized, aligned institutional frameworks (i.e., performance metrics and measurement) need to be developed in a manner that enhances academic well-being going forward.